2017
DOI: 10.1088/1361-6587/aa6c33
|View full text |Cite
|
Sign up to set email alerts
|

Low-threshold parametric decay of the ordinary wave in ECRH experiments at toroidal devices

Abstract: In this paper we analyse low-threshold parametric decay instability (PDI) of the ordinary wave infirst harmonic O-mode ECRH experiments at toroidal devices. The corresponding expressions for the PDI power threshold and its growth rate are derived analytically and evaluated numerically for the conditions of the ECRH experiments on the W7-A stellarator. The possibility of low-threshold parametric decay of the pump ordinary wave on the FTU tokamak is also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Type-2 emissions are more frequent (see Fig.3) at higher densities and when a higher dB/dt of the rotating island is measured by the reference Mirnov coil, i.e. when the magnetic island is larger, and thus the density gradient can be more easily found inverted, condition to facilitate the PDI occurrence as predicted by theory [6,7]. In any case emissions appear as spiky, with a few microseconds time-scale of temporal evolution (Fig.4).…”
Section: Emissions Of Typementioning
confidence: 79%
See 1 more Smart Citation
“…Type-2 emissions are more frequent (see Fig.3) at higher densities and when a higher dB/dt of the rotating island is measured by the reference Mirnov coil, i.e. when the magnetic island is larger, and thus the density gradient can be more easily found inverted, condition to facilitate the PDI occurrence as predicted by theory [6,7]. In any case emissions appear as spiky, with a few microseconds time-scale of temporal evolution (Fig.4).…”
Section: Emissions Of Typementioning
confidence: 79%
“…The aim was to add experimental evidences to confirm the hypotheses of low-threshold excitation of waves generated by PDI mechanisms based on the observation of back-scattered power in the case of 2 nd harmonic Xmode injection in TEXTOR [4 and reference therein], and on other observations in ASDEX-U [5]. Theoretical analysis [6,7] predicts the possibility of low-threshold parametric decay also for O-mode pump-wave injection, which can be explored at frequencies close to the first Harmonic resonance in FTU. Experiments were made at magnetic fields of 4.7 T and 3.6 T, injecting the 140 GHz probe and observing the emission from the second antenna of the EC launcher in symmetric and asymmetric configurations (see section 1.1), in presence of MHD islands mainly stimulated by Ne injection.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold in this case is higher (several hundred kW depending on the plasma parameters) than for the Xmode pump whereas the growth rate is large enough (in the range of 10 7 s -1 ) to expect the non-linear saturation of the instability [26].…”
mentioning
confidence: 81%
“…In particular it is being exploited to study possible anomalous phenomena originating from the interaction of the probe beam with the plasma, as already noticed in di erent experiments [3,4]. It has been observed that the anomalous phenomena can be driven by the inversion of the density profile induced by the presence of a well-developed magnetic island [5,6]. Since we are interested in e ects of the magnetic islands on the EC beams, in order to verify the conditions for such low-threshold PDIs and their link with an inversion of the density gradient in islands, we stimulate with various techniques the growth of a MHD rotating island, and observe the e ects of its passage through the crossing region of the probe and receiving beams.…”
Section: Introductionmentioning
confidence: 98%